Immuno-epigenetic paradigms in coronavirus infection - Gupta, Swati; Hemeg, Hassan A.; Afrin, Farhat (Frontiers in Immunology, 2025)
Coronavirus Disease 2019 (COVID-19) is caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2), a novel member of the Coronaviridae family. The viral genome encodes both structural proteins, such as spike, membrane, hemagglutinin, and envelope, as well as non-structural proteins that include auxiliary proteins and replicase essential for viral replication. While immunization campaigns have mitigated the spread of the virus, therapeutic interventions remain critical for managing outbreaks and preventing long-term health consequences. Despite extensive global research into the genome, structure, entry process, and replication mechanisms of SARS-CoV-2, key aspects such as the roles of membrane lipids in viral entry, packaging, and release, as well as the metabolic alterations in infected cells, remain poorly understood. Epigenetics, the study of heritable phenotypic changes driven by genetic and non-genetic factors, plays a pivotal role in shaping host responses to SARS-CoV-2 infection. Epigenetic modifications, such as histone methylation and acetylation, DNA and RNA methylation, chromatin remodeling, and non-coding RNA regulation, significantly influence gene expression in infected host cells. These reversible changes orchestrate the host’s antiviral responses and potentially alter susceptibility to COVID-19. This review delves into the immuno-epigenetic modifications occurring in hosts infected with SARS-CoV-2, providing insights into how these changes trigger viral replication and infection processes. By examining the current state of research on the immune-epigenetic landscape of SARS-CoV-2 infections, we highlight the mechanisms by which these modifications affect the host-viral interplay. Furthermore, we propose potential therapeutic targets within the immune-epigenetic pathways that could enhance ongoing efforts to combat COVID-19. Understanding these mechanisms will not only provide a deeper perspective on the virus’s pathogenic strategies but also offer innovative approaches to improve therapeutic interventions. By addressing the gaps in knowledge surrounding immune-epigenetic factors, this review aims to contribute to the development of novel strategies for preventing and managing coronavirus infections and its variants.